VEGF-C–induced lymphangiogenesis in sentinel lymph nodes promotes tumor metastasis to distant sites - Hirakawa, Satoshi (American Society of Hematology, 2007)
The mechanisms by which tumors metastasize to sentinel and distant lymph nodes, and beyond, are poorly understood. We developed transgenic mice that overexpress vascular endothelial growth factor-C (VEGF-C) and green fluorescent protein specifically in the skin and studied the effects of chemically-induced skin carcinogenesis in this model. We found that in contrast to VEGF-A, VEGF-C does not increase the growth of primary tumors, but instead induces expansion of lymphatic networks within sentinel lymph nodes, even before the onset of metastasis. Once the metastatic cells arrived at the sentinel lymph nodes, the extent of lymphangiogenesis at these sites increased. Of importance, in mice with metastasis-containing sentinel lymph nodes, tumors that expressed VEGF-C were more likely to metastasize to additional organs, such as distal lymph nodes and lungs. No metastases were observed in distant organs in the absence of lymph node metastases. These findings indicate an important role of VEGF-C–induced lymph node lymphangiogenesis in the promotion of cancer metastasis beyond the sentinel lymph nodes. VEGF-C is therefore a good target to slow or even prevent the onset of metastasis.